2010
DOI: 10.1088/0022-3727/43/17/175402
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electrostatic and electrohydrodynamic forces on the chaining of carbon nanofibres in liquid epoxy

Abstract: The formation of chains of aligned carbon nanofibres (CNFs) in polymers is a subject of great interest in the field of multifunctional nanocomposites. The mechanism of CNF chain assembly and growth in a low viscosity epoxy is investigated by developing a finite element model of a chain attached to an electrode. The model examines the combined effects of electrostatic and electrohydrodynamic forces on chain morphology. The electrohydrodynamic forces are modelled using the theory of ac electro-osmosis. The predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Prasse et al and Schwarz et al were the first to align carbon black (CB) particles in an oligomer fluid followed by polymerization which locks the particles in place in a polymer matrix. In the following years the idea of aligned carbon was studied further and extended to graphite sheets , carbon nanotubes (CNTs) carbon fibres and carbon cones . Common for all these reports is the use of an initial particle fraction much below the percolation threshold of the isotropic mixture, and thus initially electrically insulating mixture, and a conductivity jump due to the aligned strings forming conductive pathways through the polymerized matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Prasse et al and Schwarz et al were the first to align carbon black (CB) particles in an oligomer fluid followed by polymerization which locks the particles in place in a polymer matrix. In the following years the idea of aligned carbon was studied further and extended to graphite sheets , carbon nanotubes (CNTs) carbon fibres and carbon cones . Common for all these reports is the use of an initial particle fraction much below the percolation threshold of the isotropic mixture, and thus initially electrically insulating mixture, and a conductivity jump due to the aligned strings forming conductive pathways through the polymerized matrix.…”
Section: Introductionmentioning
confidence: 99%
“…A pair of parallel plate electrodes, in which the nanocomposite was sandwiched, has been widely employed for the electric field application. It has been reported that preferable electric field for CNT alignment in polymers had an intensity of 1 kV/cm in order of magnitude and a frequency as high as about 1 kHz [17,18]. Considering that the maximum output voltage of a commercially available high frequency (HF) voltage source is typically a few kilovolts, the size of nanocomposite, which is equal to the distance between parallel plate electrodes, has been limited to a few centimeters.…”
Section: Introductionmentioning
confidence: 99%